Compendium of maritime labour instruments. (International Labour Office, 2008)
Maritime Labour Convention, 2006; Seafarers' Identity Documents (Revised) Convention, 2003; Work in Fishing Convention and Recommendation, 2007. This essential new reference source presents the full text of the Maritime Labour Convention, 2006, along with a collection of related standards, including the Seafarers' Identity Documents Convention (Revised), 2003 (No. 185), the Work in Fishing Convention, 2007 (No. 188) and its accompanying Recommendation, as well as the ILO's fundamental Conventions and the Declaration on Fundamental Principles and Rights at Work and its follow-up.